Changes in Weddell Seal Leptonychotes weddellii (Phocidae) Behaviour at the First Stage of Ontogenesis - Smagol, V.M.; Dzhulai, A.O. (Український антарктичний журнал, 2018)
Objective. The analysis of changing the Weddell seal diurnal activity during first two weeks post partum. The «budget of time» method was used with measuring of time of different behavioral patterns (feeding, learning and motion activity, sleep). It was started since second day and measured every 5 days.